PENELITIAN AIR TANAH DI WADUK PUNTUK SURUH KECAMATAN PENGADEGAN KABUPATEN PURBALINGGA – JAWA TENGAH - Garinas, Wahyu (Jurnal Teknologi Lingkungan, 2009)
Based on groundwater indication map, the area of Pengadegan district, PurbalinggaRegency, has low groundwater resources potential for both deep and shallowgroundwater.Investigation using resistivity showed that the potential water layers were found inthe eastern part of the Dam at B and C layers. The groundwater is shallow and thethickness of the aquifer is about 20 meter and extent horizontally up to 30 meter.Layer A and B in the western part of the Dam are possibly act as a water trap asthey lies above a compact layer E.To know the potential groundwater area it is suggested that further research andsurvey be done in the eastern part of the Dam.